AYURVEDIC INTERVENTION IN THE MANAGEMENT OF INFERTILITY W.S.R. TUBAL INFERTILITY- A CASE SERIES (AYUSHDHARA, 2016)
Tubal infertility is considered as second most contributing factor in female fertility. In these cases results are very encouraging not only for removal of blockage but also for enhance the conception rate through Ayurvedic management. Mainly Vata and Kapha are responsible for tubal blockage so in these patients Apamargakshara Taila was selected for Uttarabasti because of its Vata-Kapha Shamaka and Lekhana property and Phalakalyana Ghrita was prescribed to patients for augment the conception. In these cases HSG and USG were used as diagnostic tool and to assess the results of management. Here, all three patients reported tubal blockage before treatment and the normal study was found on HSG after two sitting of Uttarabasti and also getting pregnancy after one month course of Phalakalyana Ghrita. In these cases very encouraging results were reported and it can be a standard treatment for management of female Infertility w.s.r. tubal blockage in future in routine Ayurvedic Gynecological practice. During follow-up of patients; no any abnormality was reported clinically as well as on USG.